The Authority of Notaries in Drawing Up Inheritance Certificates Made Outside the Domicile of the Deceased for Land Registration - Raudhotul Jannah Lailatul Istiqfaroh (Eduvest - Journal of Universal Studies, 2025)
An Inheritance Certificate is often required for land registration, in this case it is stated in Article 111 paragraph (1) of ATR/BPN Ministerial Regulation Number 16 of 2021 concerning land registration. And after the changes to the PMA it was stated that Notaries have the authority to make inheritance certificate deeds for all Indonesian citizens without distinguishing between population groups. However, to exercise the authority of a Notary, he must be in the same position as the testator's residence at the time of death. The problem formulation in this research is (1) What is the authority of a Notary in making a Deed of Inheritance for land for Indonesian citizens? (2) What are the legal consequences of a Deed of Inheritance Certificate made by a Notary located outside the testator's residence for land registration?. This type of research uses normative legal research, the approach used is a statutory-regulatory approach, a contextual approach. Data collection was carried out through literature study and then explained in normative juridical terms. The research results show that (1) Notaries have the authority to make inheritance certificate deeds. This is based on Article 15 of Law Number 2 of 2014 concerning the Position of Notaries, which gives authority to Notaries to make authentic deeds including inheritance certificate deeds and Article 111 paragraph ( 1) Republic of Indonesia ATR/KBPN Ministerial Regulation Number 16 of 2021 that the inheritance certificate deed made by a Notary is not only valid for Indonesian citizens of Chinese descent